Evaluation of The Effectiveness of New Connector Road in Reducing Congestion through VISSIM Simulation - Rimbawan, Ratno Damar; Prasetyo, Yohanes Pracoyo Widi; Sunarko (Journal of Development Research, 2025)
Rapid motorization in Indonesia has intensified congestion not only in metropolitan areas but also in secondary urban centers such as Genteng District, Banyuwangi, where a single arterial corridor supports commercial and inter-district mobility. However, research addressing congestion mitigation in semi-urban road networks through strategic traffic diversion remains limited. This study evaluates the effectiveness of an alternative road routing strategy in reducing congestion along Jalan Gajah Mada using VISSIM-based microscopic simulation. Two scenarios were compared: the existing condition and a diversion strategy rerouting vehicles through Jalan KH Wahid Hasyim. Key performance indicators—average travel time, speed, queue length, and level of service (LoS)—were analyzed. Results reveal significant performance improvements despite a longer physical route: travel time decreased by 25.8%, speed increased by 143.6%, queue length reduced by 44.9%, and LoS improved from E to D. These findings highlight the potential of strategically planned traffic diversion to enhance mobility in semi-urban settings. The study is limited to peak-hour traffic and a single diversion scenario, suggesting the need for further evaluation with multimodal and multi-scenario analyses.